More Support for the Dependency-Resentment Hypothesis - Paul J. Wright; Robert S. Tokunaga; Maria Rosaria Nappa; Antonio Chirumbolo; Elena Cattelino; Alessandra Ragona; Gaetano Maria Sciabica; Mara Morelli (Sexuality & Culture, 2025)
Abstract Previously in Sexuality & Culture ( S&C ), we published an article titled “On men’s problematic pornography use and hostile attitudes toward women” (Wright and Tokunaga in Sex Cult, 2025. https://doi.org/10.1007/s12119-025-10424-2 ). This article presented our first articulation of the Dependency-Resentment Hypothesis (DRH) of men’s problematic pornography use and hostile attitudes toward women. It also presented analyses of data collected in Greece (Liatsou et al. in Sex Cult 29(1):1034–1050, 2025. https://doi.org/10.1007/s12119-024-10311-2 ) that led to the articulation of the DRH. Analyses using data collected in the United States (Wright et al. in The dependency-resentment hypothesis of men’s problematic pornography use and hostile attitudes toward women, 2025. https://doi.org/10.1007/s10508-025-03269-1 ) and China (Wright et al. in J Sex Marital Ther 51(7):791–797, 2025. https://doi.org/10.1080/0092623X.2025.2556454 ) were subsequently conducted. Findings from all three datasets yielded results consistent with the DRH. We now return to the pages of S&C to report results from a fourth dataset, collected in Italy. Once again, findings were consistent with the DRH. We encourage S&C contributors to evaluate the scope and contingencies of the DRH in their own data and to develop novel hypotheses about the interrelationships between frequent pornography use, problematic pornography use, and sexual beliefs, attitudes, and behaviors.